The association between socioeconomic status and mental health = Sammenhengen mellom sosioøkonomisk status og psykisk helse - Odden, Ranveig (Universitetet i Tromsø, 2013)
Objective: The aim of this study was to examine the associations between mental health (particularly anxiety and depression) and socioeconomic status. Material and methods: Data was collected from The Tromsø Study, Tromsø 6 (2007-2008). 5 829 women and 5 580 men aged 30-87 years (57 %) were included in the study. Mental health was assessed by the Hopkins Symptom Checklist-10 (SCL-10). Two indicators of socioeconomic status were used, level of education and household income. A SCL-10 score ≥ 1.85 indicates significant mental health problems. We adjusted for age, lifestyle variables, social network variables and family history. Results: Significant mental health problems were reported by 5.9 % (95 % confidence interval: 5.3 - 6.5) of men and 10.4 % (95 % confidence interval: 9.6 - 11.2) of women. Mean SCL-10 score was for men 1.23 and 1.34 for women. Adjusted for a number of possible confounders, we found a significant inverse linear trend for household income and level of mental health problems (SCL-10 mean score) and the prevalence of significant mental health problems, in both men and women. Age-adjusted analysis showed a significant linear trend for education and level of mental problems (SCL-10 mean score) and the prevalence of significant mental health problems for both sexes. Conclusion: Mental health problems were strongly inversely associated with socioeconomic status for men and women. The strongest association was found for household income.